A multidisciplinary approach to the management of disorders of gut-brain interaction: psychopharmacology, psychotherapy, and diet - Barrera Flores, Francisco J.; Guerrero Tamez, José Adrián; Winkelman, Tatiana; Barrera Flores, Regina; Madva, Elizabeth N. (Frontiers in Gastroenterology, 2025)
IntroductionDisorders of gut-brain interaction (DGBI), including irritable bowel syndrome and functional dyspepsia, are chronic gastrointestinal syndromes characterized by visceral hypersensitivity and altered brain-gut signaling in the absence of known structural pathology. A significant proportion of individuals with DGBI have comorbid psychiatric conditions, especially anxiety and depression, highlighting the biopsychosocial underpinnings of these disorders.MethodsThis narrative review synthesizes the neurophysiological, psychological, pharmacological, and psychotherapeutic literature related to DGBI. We examined the role of gut-brain axis dysregulation, the prevalence and impact of psychiatric comorbidity, and evaluated current treatment modalities, including neuromodulators, brain-gut behavior therapies (BGBTs), and dietary interventions.ResultsNeuroimaging and genetic studies support the role of emotional and cognitive circuits in modulating gut sensitivity and symptom perception. Psychiatric comorbidity, particularly anxiety, is bidirectionally linked to DGBI and influences treatment response. Neuromodulators such as tricyclic antidepressants demonstrate modest efficacy. BGBTs—including cognitive behavioral therapy and gut-directed hypnotherapy—exhibit comparable efficacy to pharmacologic treatments, with sustained symptom relief and additional benefit on mood and illness-related beliefs.DiscussionDGBI represent complex, stress-sensitive conditions best managed through multidisciplinary care. Integration of pharmacologic neuromodulation, psychotherapeutic interventions, and dietary strategies targeting the brain-gut axis offers the most comprehensive approach. Future research should refine treatment matching based on symptom phenotype, psychological profile, and gut-brain biomarkers to improve long-term outcomes.